Market Survey Research: A model for ethnobotanical education - Nguyen, My Lien Thi; Doherty, Katherine T.; Wieting, Julia (Ethnobotany Research and Applications, 2008)
Ethnobiological imperatives in education and NSF initiatives for improving excellence in science, technology, engineering and mathematics (STEM) education for all students were addressed by the development of a research oriented, market survey ethnobotanical project developed with the involvement of undergraduate students. This market survey project presents a model for Ethnobiological and STEM education that is adaptable to educational institutions and communities world-wide. Collaboration among users of the model and synthesis of results would provide an international look at the biocomplexity of markets systems. Students gained experience in scientific research, including: observation and forming hypothesis, collection and analysis of data, and dissemination of results. Students practiced ethnobotanical research skills, including: developing and applying an informed consent statement, producing herbarium vouchers, interacting with cultural representatives. Survey materials and hypotheses were modified during the research period to maximize our efforts. Students co-authored with instructor two publications resulting from the research involvement. The instructor gained experience by involving students in research and application of the instructor’s research to an undergraduate ethnobotanical project. Challenges are discussed, as well as recommendations synthesized from these experiences and from reviews of other student-research studies.